Europium activated β-sialon phosphor and light-emitting device

By adding an appropriate amount of boron to the europium-activated β-Selon phosphor to optimize its optical performance, the problem of inconsistent optical performance in the state of powder and sheet is solved, and efficient luminescence of the light emitting device is achieved.

CN117062896BActive Publication Date: 2025-03-18DENKA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280022995.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-01-19
Publication Date
2025-03-18
Estimated Expiration
2042-01-19

AI Technical Summary

Technical Problem

In the prior art, the external quantum efficiency of the powder phosphor is inconsistent with the luminous emitting characteristics dispersed in the cured resin, resulting in the failure to fully exert the optical properties of the phosphor in the light emitting device.

Method used

By adding an appropriate amount of boron to the europium-activated β-Selon phosphor, the content of boron is controlled between 60 and 500 ppm to optimize the optical properties in the powder and sheet states.

Benefits of technology

The external quantum efficiency and luminescence characteristics of the europium-activated β-type Theron phosphor are excellent in powder and dispersed in cured resin, which improves the luminescence efficiency of the luminescence device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004458875740000151
    Figure BDA0004458875740000151
  • Figure HDA0004458875750000011
    Figure HDA0004458875750000011
Patent Text Reader

Abstract

One embodiment of the present application provides a europium-activated β-sialon phosphor comprising boron, wherein the boron content is 60 to 500 ppm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a europium-activated β-sialon phosphor and a light-emitting device. Background Art

[0002] Oxynitride phosphors are known to have a small decrease in brightness accompanying a temperature rise and to have excellent durability. Among oxynitride phosphors, europium-activated β-sialon is known to be a green phosphor that can be excited by ultraviolet light, visible light, or the like.

[0003] The β-sialon phosphor can be obtained, for example, by heating a raw material mixture containing silicon nitride powder, aluminum nitride powder, and europium oxide powder in a nitrogen atmosphere. In the research on the practical application of the β-sialon phosphor, research on improving the brightness is also being conducted.

[0004] For example, Patent Document 1 describes a method for manufacturing a β-sialon phosphor, comprising the following steps: a first heat treatment step of heat-treating a mixture containing an aluminum compound, a first europium compound, and silicon nitride to obtain a first heat-treated product, and a second heat treatment step of heat-treating the first heat-treated product and a second europium compound in a rare gas environment to obtain a second heat-treated product. In addition, Patent Document 2 proposes a method for manufacturing a β-sialon phosphor, comprising the following steps: a calcination step of calcining a raw material mixture of a β-sialon phosphor at a temperature of 1820°C to 2200°C in a nitrogen environment to obtain a calcined product, and an annealing step of annealing the calcined product at a temperature of 1100°C or higher in a reducing gas environment.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2017-002278

[0008] Patent Document 2: International Publication No. 2010 / 143590 Summary of the invention

[0009] The optical performance of phosphors is mainly evaluated based on absorption of irradiated light and quantum efficiency, but these are mainly evaluated on powders. On the other hand, phosphors used in light-emitting devices are dispersed in transparent sealing resins, etc., and the configuration environment and density of phosphors are different. Therefore, depending on the effect expected from the phosphor evaluation conducted on powders, there may be a case where the evaluation of the two is inconsistent, such as the phosphor will not fully exert itself when dispersed in a curing resin.

[0010] The object of the present application is to provide a europium-activated β-sialon phosphor having excellent external quantum efficiency in powder evaluation and excellent light-emitting properties in a state where the phosphor is dispersed in a curing resin and molded into a sheet shape.

[0011] One embodiment of the present application provides a europium-activated β-sialon phosphor containing boron, wherein the boron content is 60 to 500 ppm.

[0012] The europium-activated β-sialon phosphor can exhibit excellent external quantum efficiency as a powder by containing boron in a predetermined content, and can also exhibit excellent light-emitting properties in a state where it is dispersed in a curing resin and molded into a sheet.

[0013] The boron content is preferably 100 to 350 ppm.

[0014] The absorptivity of the europium-activated β-sialon phosphor to light of a wavelength of 600 nm is preferably 6.0% or less. The europium-activated β-sialon phosphor is a green phosphor and can further improve the external quantum efficiency by suppressing the absorption of green fluorescence at wavelengths longer than about 525 nm.

[0015] One embodiment of the present application provides a light-emitting device comprising a light-emitting element that emits primary light and a wavelength converter that absorbs a portion of the primary light and emits secondary light having a longer wavelength than the primary light; the wavelength converter includes the europium-activated β-sialon phosphor.

[0016] Since the light-emitting device includes the europium-activated β-sialon phosphor as a wavelength converter, it has excellent light-emitting efficiency.

[0017] According to the present application, a europium-activated β-sialon phosphor having excellent external quantum efficiency in powder evaluation and excellent light-emitting characteristics in a state where the phosphor is dispersed in a curing resin and molded into a sheet shape can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic diagram for explaining the measurement method when performing sheet material evaluation. DETAILED DESCRIPTION

[0019] Hereinafter, embodiments of the present invention will be described. However, the following embodiments are examples for describing the present invention, and the present invention is not limited to the following embodiments.

[0020] Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more. When a plurality of substances equivalent to each component are present in the composition, the content of each component in the composition refers to the total amount of the plurality of substances present in the composition unless otherwise specified.

[0021] One embodiment of the europium-activated β-sialon phosphor contains boron. The europium-activated β-sialon phosphor may contain β-sialon as a main crystal, or may be composed of β-sialon. The europium-activated β-sialon phosphor may contain a different phase within a range that does not impair the gist of the present application. The europium-activated β-sialon phosphor may also have a Si 6-Z Al Z O Z N 8-Z : The composition represented by the composition formula of Eu. In the above chemical composition formula, z may be 0.0<z≤4.2, or 0.0<z≤0.5. The composition of the europium-activated β-sialon phosphor can be adjusted by changing the ingredients and composition ratio of the raw material composition when producing the phosphor.

[0022] In the composition of the europium-activated β-sialon phosphor, the contents of nitrogen atoms (N) and oxygen atoms (O) can be quantified by an oxygen-nitrogen analyzer, and the contents of europium (Eu), silicon (Si), aluminum (Al), and boron (B) can be quantitatively analyzed by an ICP emission spectrometer.

[0023] The above-mentioned boron content in the europium-activated β-sialon phosphor is 60 to 500 ppm. The europium-activated β-sialon phosphor of the present application is excellent in both external quantum efficiency in powder evaluation and luminescence characteristics in a state dispersed in a curing resin and molded into a sheet. The reason for such an effect is not clear, but the inventors speculate as follows. That is, it can be speculated that in the europium-activated β-sialon phosphor of the present application, by filling the pores that will become defects in the phosphor during the manufacture of the phosphor with ions containing a specified amount of boron, the defects are reduced, the external quantum efficiency is excellent, and the energy loss caused by absorption unrelated to light conversion in the sheet evaluation is also reduced, thereby obtaining excellent luminescence characteristics.

[0024] The lower limit of the boron content can be, for example, 80 ppm or more, 90 ppm or more, or 100 ppm or more, based on the total amount of the europium-activated β-sialon phosphor. By making the lower limit of the boron content fall within the above range, the external quantum efficiency of the europium-activated β-sialon phosphor and the luminescence intensity when the phosphor is dispersed in the curing resin can be taken into account at a higher level. The upper limit of the boron content can be, for example, 450 ppm or less, 400 ppm or less, or 350 ppm or less, based on the total amount of the europium-activated β-sialon phosphor. By making the upper limit of the boron content fall within the above range, the reduction of the luminescence characteristics of the europium-activated β-sialon phosphor can be suppressed because the heterogeneous phase generated by the addition of excess boron can be suppressed and the generation of non-luminescent components can be suppressed. The boron content can be adjusted within the above range, and can be, for example, 100 to 350 ppm based on the total amount of the europium-activated β-sialon phosphor. In addition, a boron nitride container may be used in the production of the β-sialon phosphor. When no boron source is added separately, the boron content in the obtained phosphor is less than 60 ppm, and generally is about 50 ppm.

[0025] The 50% cumulative particle size (D50) in the volume-based cumulative particle size distribution of the europium-activated β-sialon phosphor can be adjusted according to the use of the phosphor, etc. The 50% cumulative particle size (D50) in the volume-based cumulative particle size distribution of the europium-activated β-sialon phosphor can be, for example, 0.1 to 50 μm, 3 to 40 μm, or 6 to 30 μm. D50 can be controlled by, for example, adjusting the conditions such as the heating temperature and heating time during the production of the phosphor, and by classification, etc.

[0026] D50 in this specification refers to the particle size when the cumulative value from the small particle size in the distribution curve of the volume-based particle size measured by the laser diffraction and scattering method reaches 50% of the total. The distribution curve of the particle size of the phosphor is carried out according to the particle size distribution measurement method using the laser diffraction and scattering method described in JIS R 1629:1997 "Particle size distribution measurement method using laser diffraction and scattering method for precision ceramic raw materials". A particle size distribution measuring device can be used in the measurement. Specifically, first, 0.1g of the phosphor to be measured is put into 100mL of ion exchange water, and a small amount of sodium hexametaphosphate is added. After being dispersed for 3 minutes using an ultrasonic homogenizer, it is used as a measurement sample, and the particle size is measured using a particle size distribution measuring device, and then D50 is determined from the obtained particle size distribution. D50 is also called the median particle size, which refers to the average particle size of the particles as the object. In addition, as a particle size distribution measuring device, for example, "Microtrac MT3300EX II" (product name) manufactured by Microtrac BEL can be used. As an ultrasonic homogenizer, for example, “Ultrasonic Homogenizer US-150E” (product name, chip size: φ20, Amplitude: 100%, oscillation frequency: 19.5 kHz, amplitude: about 31 μm) manufactured by Nippon Seiki Co., Ltd. can be used.

[0027] By making the europium-activated β-sialon contain a specified amount of boron, the absorptivity of light with a wavelength of 600nm is suppressed. The europium in the above-mentioned phosphor absorbs little light with a wavelength of 600nm, and this wavelength has little effect on the fluorescence generated by the above-mentioned phosphor. Therefore, when the absorptivity of light with a wavelength of 600nm is high, it is considered to be the absorption caused by defects or non-luminescent components, i.e., heterophases. In the europium-activated β-sialon phosphor of the present application, for example, the absorptivity of light with a wavelength of 600nm can be set to be less than 6.0%. The europium-activated β-sialon phosphor suppresses the absorption of light with a wavelength of 600nm, and is less affected by defects and non-luminescent components, i.e., heterophases, so the external quantum efficiency is more excellent.

[0028] The external quantum efficiency of the europium-activated β-sialon phosphor can be set to, for example, 63% or more, or 64% or more. Unless otherwise specified, the light absorption rate and quantum efficiency in this specification refer to the quantum efficiency obtained when the phosphor is excited by blue light of a wavelength of 455 nm. Specifically, the external quantum efficiency is measured and obtained by the method described in the examples of this specification.

[0029] The europium-activated β-sialon phosphor is not only excellent in external quantum efficiency in powder evaluation, but also excellent in luminescent properties when dispersed in a curing resin and formed into a sheet. More specifically, for a sheet comprising the above-mentioned europium-activated β-sialon phosphor and a curing resin, when light of a wavelength of 455nm is irradiated on the sheet, a larger light beam (unit: lm) than that of the existing europium-activated β-sialon phosphor is generated. Therefore, when the europium-activated β-sialon phosphor of the present application is used, a brighter light-emitting element can be prepared than when using an existing phosphor, which is beneficial in practice.

[0030] The europium activated β-sialon phosphor can be used alone or in combination with other phosphors. The europium activated β-sialon phosphor is preferably used in light-emitting devices such as LEDs because of its excellent internal quantum efficiency. The phosphor can also be dispersed in a curing resin for use. The curing resin is not particularly limited, and for example, a resin used as a sealing resin for a light-emitting device can be used.

[0031] One embodiment of the light-emitting device is a light-emitting device having a light-emitting element that emits primary light, and a wavelength converter that absorbs a portion of the primary light and emits secondary light having a longer wavelength than the wavelength of the primary light. The wavelength converter includes the europium-activated β-sialon phosphor. The light-emitting element that emits primary light may be, for example, an InGaN blue LED. The light-emitting element and the wavelength converter may also be dispersed in a sealing resin or the like. As the sealing resin, it is desired that it is colorless in itself, and a sealing resin with excellent transmittance to visible light wavelengths may be used. The sealing resin may generally be a sealing resin that is considered to be transparent. As the resin as described above, for example, a silicone resin or an acrylic resin may be used.

[0032] The europium-activated β-sialon phosphor of the present application can be manufactured, for example, by the following method. As an example of a method for manufacturing a europium-activated β-sialon phosphor, it may be a method having the following steps: a step of obtaining a sintered body of β-sialon from a raw material composition containing a silicon source, an aluminum source, and a europium source and a nitride of at least one of these by one or more heat treatments (hereinafter also referred to as a calcination step); and a step of obtaining an annealed body from a compound containing the above-mentioned sintered body and boron as a constituent element by one or more annealing treatments in a gas environment containing at least one selected from a rare gas, a reducing gas, and an inactive gas (hereinafter also referred to as an annealing step). This example is described below.

[0033] The raw material composition contains a compound having an element that will become a constituent element of europium-activated β-sialon, and contains at least a silicon source, an aluminum source, and a europium source. In the raw material composition, at least one of the silicon source, the aluminum source, and the europium source is a nitride. The nitride is also a nitrogen source because it contains nitrogen that will become a constituent element of europium-activated β-sialon. The silicon source refers to a compound or monomer having silicon as a constituent element, the aluminum source refers to a compound or monomer having aluminum as a constituent element, and the europium source refers to a compound or monomer having europium as a constituent element.

[0034] In this specification, a compound containing silicon as a constituent element is also referred to as a silicon compound, a compound containing aluminum as a constituent element is also referred to as an aluminum compound, and a compound containing europium as a constituent element is also referred to as a europium compound. The silicon compound, the aluminum compound, and the europium compound may each be any one of a nitride, an oxide, a nitrogen oxide, and a hydroxide. In addition, the raw material composition may further contain β-Sialon or europium-activated β-Sialon. Here, β-Sialon or europium-activated β-Sialon is a material that becomes a skeleton or a core.

[0035] Examples of silicon compounds include silicon nitride (Si 3 N 4 ) and silicon oxide (SiO 2 ) etc. As silicon nitride, it is preferred to use silicon nitride with a higher α fraction. The α fraction of silicon nitride can be, for example, 80% by mass or more, 90% by mass or more, or 95% by mass or more. If the α fraction of silicon nitride falls within the above range, primary particle growth can be promoted. As silicon nitride, it is preferred to use silicon nitride with a lower oxygen content. The oxygen content of silicon nitride can be, for example, less than 3.0% by mass, or less than 1.3% by mass. If the oxygen content of silicon nitride falls within the above range, the generation of defects in the crystallization of β-sialon can be suppressed.

[0036] Examples of aluminum compounds include aluminum nitride (AlN), aluminum oxide (Al 2 O 3 ), and aluminum hydroxide (Al(OH) 3 )wait.

[0037] Examples of europium compounds include europium oxides (europium oxide), europium nitrides (europium nitride), and europium halides. Examples of europium halides include europium fluoride, europium chloride, europium bromide, and europium iodide. The europium compound preferably contains europium oxide. The valence of europium in the europium compound may be divalent or trivalent, preferably divalent.

[0038] The raw material mixture can be prepared by weighing each compound and mixing. For mixing, a dry mixing method or a wet mixing method can be used. The dry mixing method can be, for example, a method of mixing the components using a V-type mixer or the like. The wet mixing method can be, for example, a method of adding a solvent such as water or a dispersion medium to prepare a solution or slurry and mixing the components, and then removing the solvent or the dispersion medium.

[0039] The heating temperature in the calcining step may be, for example, 1800 to 2500° C., 1800 to 2400° C., 1850 to 2100° C., 1900 to 2100° C., 1900 to 2050° C., or 1920 to 2050° C. By setting the heating temperature in the calcining step to 1800° C. or higher, the particle growth of β-Sialon can be promoted, and the solid solution amount of europium can be made more sufficient. By setting the heating temperature in the calcining step to 2500° C. or lower, the crystal decomposition of β-Sialon can be sufficiently suppressed.

[0040] From the viewpoint of promoting the primary particle growth of β-Sialon, the heating time in the calcination step is preferably as long as possible. However, since crystal defects increase if the heating time is too long, the heating time may be, for example, 1 to 30 hours, 3 to 25 hours, or 5 to 20 hours.

[0041] The heating of the raw material mixture in the calcination process can be carried out, for example, under a nitrogen environment. By heating under conditions of high nitrogen partial pressure, the decomposition of silicon nitride at high temperatures can be suppressed. In addition, by treating at high temperatures, particle growth can be promoted. The heating of the raw material mixture in the calcination process can be carried out, for example, under pressure. The pressure at this time can be, for example, 0.01 to 200 MPaG, 0.02 to 200 MPaG, 0.1 to 200 MPaG, 0.1 to 100 MPaG, 0.1 to 50 MPaG, 0.1 to 15 MPaG, or 0.1 to 5 MPaG.

[0042] The number of times of heat treatment in the calcination step may be once, but may be, for example, twice or more, 2 to 5 times, or 2 to 4 times. By performing heat treatment multiple times, a europium-activated β-sialon phosphor with better luminescence intensity can be obtained.

[0043] The calcination process is subjected to more than one heat treatment, but when multiple heat treatments are performed, they may be sequentially referred to as the first heat treatment, the second heat treatment, etc., and the processes for performing each heat treatment may be sequentially referred to as the first calcination process, the second calcination process, etc. For example, when the above-mentioned manufacturing method performs two heat treatments in the calcination process, the calcination process may also be referred to as comprising: a process of subjecting the raw material composition containing nitrides to a first heat treatment to obtain a first heat treatment body; and a second calcination process of subjecting the above-mentioned first heat treatment body to a second heat treatment to obtain a second heat treatment body. In addition, at this time, the second heat treatment body is equivalent to a sintered body containing β-sialon. Before performing multiple heat treatments, the silicon source, the aluminum source, and the europium source may be mixed again and then heat treated.

[0044] When the calcining process is subjected to heat treatment for more than two times, the heating temperature, heating time, gas environment during heating, and pressure during heating of the first calcining process may be respectively applied to the heating temperature, heating time, gas environment during heating, and pressure during heating in the above-mentioned heating process. In addition, the heating temperature, heating time, gas environment during heating, and pressure during heating after the second calcining process may be the same as or different from those of the first calcining process. However, even if the heating temperature, heating time, gas environment during heating, and pressure during heating after the second calcining process are different from those of the first calcining process, they are still within the range of the conditions shown for the above-mentioned heating process.

[0045] The sintered body obtained in the calcining step is a solid solution having a crystal of β-sialon, in which an element that will become a luminescence center is solid-dissolved in a part, and the sintered body itself emits fluorescence. The sintered body obtained by the calcining step may be in a block shape, and the particle size may be adjusted by crushing before the annealing step.

[0046] Next, an annealing step is performed. The annealing step in the manufacturing method of this example is a step of annealing a mixture containing the sintered body obtained in the calcining step and a compound having boron as a constituent element. In the annealing step, an annealed body is obtained from the mixture through one or more heating treatments.

[0047] The compound having boron as a constituent element may be, for example, an oxide, a nitride, an oxygen-containing acid, etc., preferably an oxygen-containing acid. The compound having boron as a constituent element may be, for example, boron oxide (B 2 O 3 ), boron nitride (BN), and boric acid (H 3 BO 3 ).

[0048] The amount of the compound having boron as a constituent element relative to the total amount of the above-mentioned mixture can be, for example, 0.05 to 0.70 mass %, 0.07 to 0.65 mass %, or 0.08 to 0.60 mass %. By setting the above-mentioned amount to more than 0.05 mass %, boron can be further easily introduced into the phosphor, and the external quantum efficiency of the obtained europium-activated β-sialon phosphor can be further improved. If the above-mentioned amount is set to less than 0.70 mass %, the reduction of the luminescent characteristics of the obtained europium-activated β-sialon phosphor can be suppressed. Depending on the type of the compound having boron as a constituent element, the composition ratio of boron will be different, so the preferred amount can be adjusted within the above range.

[0049] The annealing step is performed in a gas environment containing at least one selected from a rare gas, a reducing gas, and an inactive gas. By performing the annealing process in a gas environment containing a rare gas, a reducing gas, or an inactive gas, the ratio of divalent europium in europium in the solid solution can be increased.

[0050] The above-mentioned rare gas may contain, for example, argon and helium, may contain argon, or may be composed of argon. The above-mentioned reducing gas may contain, for example, ammonia, hydrocarbons, carbon monoxide, and hydrogen, may contain hydrogen, or may be composed of hydrogen. The inert gas may contain, for example, nitrogen, or may be composed of nitrogen. The gas environment of the annealing process may also be a mixed gas of two or more of the above-mentioned rare gas, the above-mentioned reducing gas, and the inert gas. When the gas environment of the annealing process is set to the above-mentioned mixed gas, the content of the above-mentioned reducing gas is based on the overall volume of the mixed gas, for example, it can be 1 to 50 volume %, or 4 to 20 volume %. The content of the above-mentioned inert gas is based on the overall volume of the mixed gas, for example, it can be 1 to 50 volume %, or 4 to 20 volume %. The volumes of the above-mentioned reducing gas, inert gas, and mixed gas are values ​​based on the volumes of the standard state.

[0051] The pressure during the annealing treatment may be the same as the pressure in the calcining step, but is preferably lower than the pressure conditions in the calcining step, and more preferably atmospheric pressure.

[0052] The temperature of the annealing treatment must be set lower than the heating temperature in the calcining process. The upper limit of the temperature of the annealing treatment may be, for example, below 1700°C or below 1680°C. By setting the upper limit of the temperature of the annealing treatment within the above range, the further growth of particles in the sintered body, the agglomeration between solid solutions, the formation of secondary particles and the like can be suppressed, and the coarsening of particles can be suppressed. The lower limit of the temperature of the annealing treatment may be, for example, above 1000°C, above 1100°C, above 1200°C, above 1300°C, or above 1400°C. By making the lower limit of the temperature of the annealing treatment fall within the above range, the crystal defect density of the β-sialon contained in the annealed body can be reduced, and the quantum efficiency can be further improved. The temperature of the annealing treatment can be adjusted within the above range, for example, it may be 1000-1700°C, or 1100-1680°C.

[0053] From the viewpoint of further reducing crystal defects in the phosphor contained in the annealed body, the heating time in the annealing treatment may be, for example, 1 to 30 hours, 2 to 25 hours, or 3 to 20 hours.

[0054] The annealing process is an annealing process performed more than once. When multiple annealing processes are performed, they may be sequentially referred to as the first annealing process, the second annealing process, etc., and the processes for performing each annealing process may be sequentially referred to as the first annealing process, the second annealing process, etc. For example, when the annealing process is performed twice in the above-mentioned manufacturing method, the annealing process may also be referred to as including: a process of performing a first annealing process on the sintered body to obtain a first annealed body; and a second annealing process of performing a second annealing process on the first annealed body to obtain a second annealed body. Then, at this time, the second annealed body is equivalent to the above-mentioned annealed body.

[0055] When the annealing process is performed more than twice, the temperature, heating time, and pressure during heating of the annealing process in the first annealing process can be respectively applied to the temperature, heating time, and pressure during heating of the annealing process in the above annealing process. Moreover, the temperature, heating time, and pressure during heating of the annealing process after the second annealing process can be the same as or different from those of the first annealing process. However, even if the temperature, heating time, and pressure during heating of the annealing process after the second annealing process are different from those of the first annealing process, they are still set within the range of the conditions shown for the above annealing process.

[0056] The number of annealing treatments in the annealing step may be 1, but may be 2 or more, for example, 2 to 5, or 2 to 4. By performing multiple annealing treatments, the crystal defect density of the β-sialon contained in the annealed body is reduced, and a europium-activated β-sialon phosphor having a better quantum efficiency can be obtained.

[0057] When multiple annealing treatments are performed in the annealing process, the above-mentioned compounds having boron as a constituent element may be blended at once in the first annealing process, or may be blended in batches in multiple annealing processes, but preferably are blended at once in the first annealing process. In addition, when these compounds are blended in batches, the description of the total blending amount of the compounds having boron as a constituent element may be understood as the total amount of the compounds having boron as a constituent element blended in multiple annealing processes and applied.

[0058] The method for producing a europium-activated β-sialon phosphor may include other steps in addition to the calcination step and the annealing step. As other steps, for example, there may be a step of treating the annealed body obtained in the annealing step with at least one of an acid and an alkali, a classification step of adjusting the particle size of the annealed body or the annealed body after the acid treatment, etc. The step of treating the annealed body with an acid is called an acid treatment step, and the step of treating the annealed body with an alkali is called an alkali treatment step.

[0059] By the acid treatment process or the alkali treatment process, for example, the crystal defect density in the phosphor contained in the annealed body can be further reduced, silicon existing on the surface of the solid solution generated by thermal decomposition of β-sialon can be removed, and the pseudo-polymorphic AlN polytype (polytypoid) of aluminum nitride (AlN) generated as a by-product during the preparation of the first sintered body can be removed. The acid can include, for example, hydrofluoric acid and nitric acid. The acid can also be a mixed acid of hydrofluoric acid and nitric acid. The alkali can include, for example, sodium hydroxide.

[0060] The classification process can be performed by, for example, a wet classification method or a dry classification method. As wet classification, for example, the annealed body is added to a mixed solvent containing ion exchange water and a dispersant (such as sodium hexametaphosphate, etc.), or added to a mixed solvent containing ion exchange water and ammonia water, and then stirred and then allowed to stand to remove particles with a small particle size by elutriation classification.

[0061] Although several embodiments have been described above, the present application is not limited to the above embodiments. In addition, the descriptions of the above embodiments are applicable to each other.

[0062] Example

[0063] Hereinafter, the present invention will be described in more detail with reference to the following examples and comparative examples. However, the present invention is not limited to the following examples.

[0064] (Comparative Example 1)

[0065] [Preparation of Europium-activated β-sialon phosphor]

[0066] Silicon nitride (Si 3 N 4 , α fraction: 95 mass%, oxygen content: 1.3 mass%) 96.0 mass%, aluminum nitride (AlN) 2.8 mass%, aluminum oxide (Al 2 O 3 ) 0.5 mass%, and europium oxide (Eu 2 O 3 ) 0.7 mass % each raw material was weighed into a container and mixed by a V-type mixer (manufactured by Tsutsui Rikagaku Kikai Co., Ltd.) to obtain a mixture. The obtained mixture was completely passed through a sieve with a mesh of 250 μm to remove agglomerates to obtain a raw material composition. Agglomerates that did not pass through the sieve were crushed and the particle size was adjusted so that it could pass through the sieve.

[0067] Weigh 200 g of the raw material composition prepared as described above into a cylindrical boron nitride container with a lid (manufactured by DENKA Corporation, a molded product with boron nitride (trade name: DENKA boron nitride N-1) as the main component, inner diameter: 10 cm, height: 10 cm). Then, place the container in an electric furnace equipped with a carbon heater, heat it to 2020°C under a nitrogen environment (pressure: 0.90 MPaG), and heat it at a heating temperature of 2020°C for 8 hours (calcination process). After heating, take the sample that slowly agglomerates into a block in the above container into a mortar and crush it. After crushing, pass it through a sieve with a mesh of 250 μm to obtain a powdery first sintered body.

[0068] Next, the first sintered body is filled in a cylindrical boron nitride container, and the container is placed in an electric furnace equipped with a carbon heater. The temperature is raised to 1450°C in an argon gas environment (pressure: 0.025 MPaG), and the heating is performed at 1450°C for 3 hours (annealing process). After heating, the agglomerates of particles are gradually agglomerated in the container, crushed with a mortar, and passed through a 250 μm sieve to obtain a powder.

[0069] Next, the obtained powder is added to a mixed acid of hydrofluoric acid (concentration: 50% by mass) and nitric acid (concentration: 70% by mass) (hydrofluoric acid and nitric acid are mixed in a volume ratio of 1:1), and the acid treatment is performed for 30 minutes while stirring at a temperature of 75°C. After the acid treatment, the stirring is stopped and the powder is precipitated, and the supernatant and the fine powder purified by the acid treatment are removed. Thereafter, distilled water is further added and stirred again. The stirring is stopped to precipitate the powder and the supernatant and fine powder are removed. This operation is repeated until the pH of the aqueous solution becomes 8 or less and the supernatant becomes transparent, and the obtained precipitate is filtered and dried to obtain a europium-activated β-sialon phosphor.

[0070] (Example 1)

[0071] In the annealing step, the amount of boric acid blended is adjusted to be equal to the first sintered body and the amount of boric acid (H 3 BO 3 After preparing a mixture by adding boric acid in a manner that the total amount of ) is 0.1 mass % with respect to 100 mass %, the mixture was heated in a hydrogen atmosphere. The same procedure as in Comparative Example 1 was performed to obtain a europium-activated β-sialon phosphor.

[0072] (Example 2)

[0073] A europium-activated β-sialon phosphor was obtained in the same manner as in Example 1 except that the blending amount of boric acid was changed to 0.5 mass %.

[0074] (Comparative Example 2)

[0075] A europium-activated β-sialon phosphor was obtained in the same manner as in Example 1 except that the blending amount of boric acid was changed to 1.0 mass %.

[0076] (Comparative Example 3)

[0077] As the phosphor of Comparative Example 3, a standard sample of β-sialon phosphor (manufactured by Sialon Corporation, NIMS Standard Green lot No. NSG1301) was used.

[0078] <Determination of Boron Content>

[0079] The boron content of each of the europium-activated β-sialon phosphors prepared in Examples 1 and 2 and Comparative Examples 1 and 2, and the phosphor of Comparative Example 3 was measured by the following method.

[0080] First, a europium-activated β-sialon phosphor was dissolved by a pressurized acid decomposition method to prepare a sample solution, and the obtained sample solution was subjected to quantitative element analysis using an ICP emission spectrometer (manufactured by Shimadzu Corporation, model: ICPE-9000) to determine each constituent element including boron.

[0081] [Evaluation of Europium-activated β-sialon phosphor]

[0082] The europium-activated β-sialon phosphors prepared in Examples 1 and 2 and Comparative Examples 1 and 2, and the phosphor of Comparative Example 3, were evaluated for absorbance after irradiation with excitation light of a wavelength of 455 nm, internal quantum efficiency, external quantum efficiency, chromaticity X, and absorbance after irradiation with excitation light of a wavelength of 600 nm by the methods described below. The results are shown in Table 1.

[0083] <Absorption rate, internal quantum efficiency and external quantum efficiency>

[0084] The absorptivity (excitation light absorptivity), internal quantum efficiency and external quantum efficiency of the fluorescent body after irradiation with excitation light of wavelength 455nm are calculated according to the following steps. First, the fluorescent body to be measured is filled in a concave groove in a manner that the surface becomes smooth, and is installed in the opening of an integrating sphere. Monochromatic light from a Xe lamp as a light source and split into 455nm wavelength is introduced into the above-mentioned integrating sphere using an optical fiber as the excitation light for the fluorescent body. This excitation light, i.e., monochromatic light, is irradiated on the fluorescent body to be measured, and the fluorescence spectrum is measured. For the measurement, a spectrophotometer (manufactured by Otsuka Electronics Co., Ltd., model: MCPD-7000) is used.

[0085] The luminous intensity of the phosphor is determined from the data of the obtained fluorescence spectrum. In addition, the number of excitation reflected light photons (Qref) and the number of fluorescence photons (Qem) are calculated from the data of the obtained fluorescence spectrum. The number of excitation reflected light photons is calculated in the same wavelength range as the number of excitation light photons, and the number of fluorescence photons is calculated in the range of 465 to 800 nm. In addition, using the same device, a standard reflector with a reflectivity of 99% (manufactured by Labsphere, Spectralon (registered trademark)) is installed at the opening of the integrating sphere, and the spectrum of the excitation light with a wavelength of 455 nm is measured. At this time, the number of excitation light photons (Qex) is calculated from the spectrum in the wavelength range of 450 to 465 nm.

[0086] From the above calculation results, the absorptivity of the 455 nm excitation light and the internal quantum efficiency of the phosphor to be measured were determined based on the following formula.

[0087] Absorption rate of 455nm excitation light = ((Qex-Qref) / Qex)×100

[0088] Internal quantum efficiency = (Qem / (Qex-Qref)) × 100

[0089] External quantum efficiency = (Qem / Qex) × 100

[0090] In addition, the relationship between the external quantum efficiency, the absorptivity of the excitation light of 455 nm, and the internal quantum efficiency can be expressed as follows from the above formula.

[0091] External quantum efficiency = 455nm light absorption rate × internal quantum efficiency

[0092] <Chroma X>

[0093] The chromaticity X is obtained by measuring and calculating the CIE chromaticity coordinate x value (chromaticity X) in the XYZ colorimetric system specified in JIS Z8781-3:2016 "Colorimetry - Part 3: CIE tristimulus values" based on the spectral data in the wavelength region of 465 to 780 nm of the fluorescence spectrum according to the method described in JIS Z 8724:2015 "Methods for determination of color - Illuminant color".

[0094] <600nm light absorption rate>

[0095] A standard reflector with a reflectivity of 99% (Spectralon (registered trademark) manufactured by Labsphere) was installed at the side opening of the integrating sphere. Monochromatic light from a light source (Xe lamp) with a wavelength of 600 nm was introduced into the integrating sphere through an optical fiber, and the reflected light spectrum was measured by a spectrophotometer (MCPD-7000 manufactured by Otsuka Electronics Co., Ltd.). At this time, the number of incident light photons (Qex(600)) was calculated from the spectrum in the wavelength range of 590 to 610 nm.

[0096] Next, after the β-sialon phosphor is filled in the concave groove in a smooth surface and installed in the opening of the integrating sphere, a monochromatic light with a wavelength of 600nm is irradiated, and the incident reflected light spectrum is measured by a spectrophotometer. The incident reflected light photon number (Qref(600)) is calculated from the obtained spectral data. The incident reflected light photon number (Qref(600)) is calculated within the same wavelength range as the incident light photon number (Qex(600)). The 600nm light absorptivity is calculated based on the following formula from the two obtained photon numbers.

[0097] 600nm light absorption rate = ((Qex(600)-Qref(600)) / Qex(600))×100

[0098] Regarding the measured values ​​of the absorptivity, internal quantum efficiency, external quantum efficiency, and chromaticity X of the phosphor, if the manufacturer, manufacturing lot number, etc. of the measuring device are changed, the values ​​may change. Therefore, as various measured values, the values ​​measured by the measuring method described in this specification are used. However, when the manufacturer, manufacturing lot number, etc. of the measuring device are changed, the measured values ​​obtained according to the standard sample of the above-mentioned β-sialon phosphor can also be used as the reference value to correct the various measured values. As the standard sample for obtaining the reference value, the standard sample of the β-sialon phosphor listed as the above-mentioned comparative example 3 can be used.

[0099] <Sheet material evaluation>

[0100] The sheet evaluation was performed by the method described below using the europium-activated β-sialon phosphors prepared in Examples 1 and 2 and Comparative Examples 1 and 2, and the phosphor of Comparative Example 3. The results are shown in Table 1.

[0101] First, the sample for evaluation was prepared according to the following steps. 40 parts by mass of the europium-activated β-sialon phosphor and 60 parts by mass of a silicone resin (manufactured by Toray Dow Corning Co., Ltd., trade name: OE-6630) were weighed into a container, and stirred and degassed using a rotational and revolving mixer (manufactured by THINKY, model: ARE-310) to prepare a mixture. Stirring was performed at a rotation speed of 2000 rpm for 2 minutes and 30 seconds, and degassed at a rotation speed of 2200 rpm for 2 minutes and 30 seconds.

[0102] The mixture prepared as described above is dripped onto a transparent fluororesin film (manufactured by Fluon Chemical Co., trade name: NR5100-003:100P), and another fluororesin film is stacked on the dripped product to obtain a laminated body with a liquid film formed between the two fluororesin films. The thickness of the liquid film between the fluororesin films is adjusted by passing the laminated body between two rollers with a predetermined gap. In addition, the gap between the rollers is set to a value obtained by adding 40 μm to twice the thickness of the fluororesin film.

[0103] Next, the laminate was heated at 150° C. for 60 minutes to cure the silicone resin. The two fluororesin films were then peeled off to obtain a cured sheet as an evaluation sample. The thickness of the obtained cured sheet was 40±4 μm.

[0104] The obtained evaluation sample was irradiated with excitation light, and the light beam emitted from the sheet was measured. Figure 1 A schematic diagram for explaining a measuring method for evaluating a sheet is shown. An evaluation device 200 includes a base 10, a light emitting element 30 disposed at the center of the base 10, and a setting table 20 for setting an evaluation sample disposed on the base 10 so as to surround the light emitting element. The evaluation sample 100 is set on the evaluation device 200. A blue light emitting diode is used as the light emitting element 30, and the distance t between the blue light emitting diode and the bottom surface of the evaluation sample is set to 2 mm.

[0105] The evaluation sample 100 was irradiated with excitation light of a wavelength of 455 nm from below, and a light beam Ig of a light of a wavelength of 500 to 800 nm emitted from the top surface (the main surface on the opposite side to the light emitting element side) of the evaluation sample 100 was measured. The light beam was measured using a total light beam measurement system (model: HM-9030) manufactured by Otsuka Electronics Co., Ltd.

[0106] The blue light-emitting diode used in the measurement had a peak wavelength of 455 nm, a chromaticity x of 0.145 to 0.165, and a chromaticity y of 0.023 to 0.037 (model: SMT type, PLCC-6, 0.2 W, SMD 5050LED).

[0107]

[0108] Industrial Applicability

[0109] According to the present application, a europium-activated β-sialon phosphor having excellent external quantum efficiency in powder evaluation and excellent light-emitting characteristics in a state where the phosphor is dispersed in a curing resin and molded into a sheet shape can be provided.

[0110] Explanation of symbols

[0111] 10 ... stand, 20 ... installation table, 30 ... light emitting element, 100 ... evaluation sample, 200 ... evaluation device.

Claims

1. A europium-activated β-sialon phosphor, It has Si 6-Z Al Z O Z N 8-Z : The composition represented by the composition formula of Eu, In the composition formula, z is 0.0<z≤4.2, The 50% cumulative particle size in the volume-based cumulative particle size distribution of the europium-activated β-sialon phosphor is 3 to 40 μm, The europium-activated β-sialon phosphor contains boron, and the content of the boron is 60 to 500 ppm.

2. The europium-activated β-sialon phosphor according to claim 1, wherein The boron content is 100-350 ppm.

3. The europium-activated β-sialon phosphor according to claim 1 or 2, wherein The absorptivity for light with a wavelength of 600 nm is 6.0% or less.

4. A light emitting device comprising a light emitting element and a wavelength converter, wherein the light emitting element emits primary light, and the wavelength converter absorbs a portion of the primary light and emits secondary light having a longer wavelength than the primary light; The wavelength converter includes the europium-activated β-sialon phosphor according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • MANUFACTURING METHOD OF β SIALON PHOSPHOR

    JP2017002278A

  • Β-sialon phosphor, use thereof and method for producing same

    WO2010143590A1

  • Nitrogen oxide phosphor and light emitting device using the same

    CN106753346A